Entrepreneurial Competence: The Experience of iNNoVaNDiS - Ibáñez-Romero, Asunción (2018)
This article describes the profile of the entrepreneur from an academic perspective, for its subsequent comparison with the way in which these skills are developed in the Specialization in Innovation and Entrepreneurship Degree (iNNoVaNDiS Program) of Universidad de Deusto at its San Sebastian campus (Spain). This program develops and promotes entrepreneurial behavior among all students in campus, working on knowledge, skills, attitudes, values, and emotions related to it. The article shares the bases and philosophy of the program. It also contrasts the previous bases vis a vis the alumni of the said program (48 students: 54% men and 46% women) discussing what has meant for them to participate in iNNoVaNDiS. The answers obtained from these individuals who are currently working in different countries, sectors, and positions allows to identify which of the competences that are worked in the program are most valued by the labor market.